IMPLEMENTASI PARADIGMA PEDAGOGI REFEKTIF (PPR) PADA MATERI BILANGAN RASIONAL DI SMP ADVENT BANDAR LAMPUNG - Tarigan, Omry; Santoso, Eko Budi (Sanata Dharma University, 2025)
This study aims to implement the Reflective Pedagogy Paradigm (PPR) in mathematics learning, specifically on rational number material in class VII of SMP Advent Bandar Lampung. PPR emphasizes holistic learning through five main stages: context, experience, reflection, action, and evaluation, with the aim of forming competent, conscientious, compassionate, and committed students. This study is a qualitative study. Research data were collected through observation, student reflection, and work results in the Student Worksheet (LKPD). The results of the study indicate that the application of PPR through the Problem-Based Learning (PBL) model can improve understanding of mathematical concepts, critical thinking skills, collaboration between students, and attitudes of responsibility and discipline. Meanwhile, the student's reflection reflects active involvement in the contextual and meaningful learning process. Therefore, it can be concluded that the implementation of PPR contributes to improving learning outcomes.